Well + good : 100 healthy recipes + expert advice for better living - Brue, Alexia; Gelula, Melisse; Miller, Johnny (Clarkson Potter/Publishers, 2019)
"From the trusted, influential, and famously trend-setting website comes the first ever Well+Good cookbook. Founders Alexia Brue and Melisse Gelula have curated a collection of 100 easy and delicious recipes from the luminaries across their community to help you eat for wellness. These dishes don't require a million ingredients or crazy long prep times. They are what the buzziest and busiest people in every facet of the wellness world- ;fitness, beauty, spirituality, women's health, and more--cook for themselves. Enjoy Venus Williams' Jalapeno Vegan Burrito, Kelly LeVeque's Chia + Flax Chicken Tenders, Drew Ramsey's Kale Salad with Chickpea Croutons, and Gabrielle Bernstein's Tahini Fudge, among many other recipes for every meal and snack time,"--Amazon.com.